2018
DOI: 10.11606/issn.1678-4456.bjvras.2018.122274
|View full text |Cite
|
Sign up to set email alerts
|

Detection of canine anti-DEA 1 antibodies using flow cytometry in dogs following DEA 1-positive blood transfusion

Abstract: The shortage of blood donor dogs in veterinary emergencies can lead to blood transfusions between animals whose blood type has not been identified. The antibody profile serves as a warning sign for animals that require a second blood transfusion, which is only advisable from compatible donor dogs. This article focuses on the determination of anti-DEA 1 antibodies using the flow cytometry technique in dogs that have undergone a transfusion using DEA 1-positive blood, compared to results obtained from crossmatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In order to carry out the hemagglutination tests and the flow cytometry, samples of canine antisera from post-transfused dogs with DEA 1 blood type were submitted to the investigation of antibodies by flow cytometry as a follow-up of alloimmunization of these respective dogs (Santos et al, 2018). Each antiserum had its own average fluorescence intensity, ranging from 15 to 538.99 and representing the concentrations of anti-DEA 1 antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to carry out the hemagglutination tests and the flow cytometry, samples of canine antisera from post-transfused dogs with DEA 1 blood type were submitted to the investigation of antibodies by flow cytometry as a follow-up of alloimmunization of these respective dogs (Santos et al, 2018). Each antiserum had its own average fluorescence intensity, ranging from 15 to 538.99 and representing the concentrations of anti-DEA 1 antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The sera were then twice washed with saline solution at 2200 x g for 3 minutes. Then, all vials were resuspended in 300 μL of saline and, finally, the readings were taken on the cytometer (Santos et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The first method described in 1999 was the Michigan State University test (MSU), in which polyclonal antiserum reagents against DEA 1, DEA 3, DEA 4, DEA 5, and DEA 7 were used [ 21 , 22 ]. Other methods for the determination of blood groups were provided for the use of monoclonal sera [ 22 , 23 , 24 , 25 , 26 ]. According to our bibliographic research, the first reported method featuring the use of monoclonal sera is RapidVet-H, which uses the agglutination reaction between the DEA 1.1 antigen and a monoclonal antibody to classify dogs as either positive or negative for DEA 1.1.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the typing card test and the gel column method were reported—the first as an agglutination-based reaction featuring the use of monoclonal antibodies [ 20 ], and the second based on agglutination in micro-columns using DEA 1.1 monoclonal antibodies within a gel matrix [ 20 , 23 ]. The tube test was used in 2006 with four monoclonal antibodies [ 24 ], and in 2011, flow cytometry was reported as a new method for hematology—not only to identify cell phenotypes but also to detect antibodies via the monoclonal murine anti-DEA 1 antibody [ 12 , 23 , 25 ]. Studies demonstrated that the flow cytometry technique has high specificity and sensitivity compared to other methods [ 12 , 19 , 23 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation